POETRY OF THE SINGING PALM TREE: THE TRADITION OF TAPPING PALM TREES IN SABU RAIJUA, NTT - Jacob, Daniel Hariman (International Review of Humanities Studies, 2024)
This article is a research study focusing on the poetry singing performed by palm sap tappers in Sabu Raijua, which has become the identity of the people of Sabu Raijua, NTT. The poems that are sung are part of the process of tapping palm sap. This tradition has become the identity of the Sabu (Do Hawu) people. This research aims to show which poems are sung by the Sabu people while tapping palm sap and examine these poems using a literary and oral tradition approach. Additionally, this article reveals the poems of the Palm Tree Song (Alure Pakolo Due) in the Sabu community as the identity of the Sabu Raijua community. It explores how the Sabu people inherit poetry and create new songs based on the mood of the lontar tapper when he is on the lontar. In this research, several concepts and theories are used, including oral tradition, tradition, ritual, folk song poetry, and cultural identity. Qualitative approach is used in this research. All data obtained was based on interviews and face-to-face interactions. This research is a case study which aims to observe and analyze the tradition of singing on palm trees and the poems sung by palm tree tappers in Sabu Raijua using an oral tradition approach. Through an ethnographic approach, local people's knowledge about the lyrics of palm tree songs and cultural identity can be revealed. The results of the research show that the tradition of singing while tapping palm sap has made this tradition the identity of the Sabu (Do Hawu) people, namely Rai Hawu, Rai Due Nga Donahu (Sabu Island, Lontar Island, and Sugar).